The Design of Bali Island Tourism Animation As a Media for Promotion of Tourism - Bayu Pratama, Rakha; Pramono, Andy; Samudro, Joko (KnE Social Sciences, 2020)
The tourist animation created for Bali Island is one of the promotional media used by the tourism sector. This animation presents information on various tourist attractions in Bali. In this case, it was supported by previous research by Niko Kurniawan with the theme of 3D Ergonomic patterns, and supported by Andy Pramono’s article themed 3D Animation using keyframe parameters. This animation visualization process is based on the source of the video that was made before, namely Bali Island Infographics by Afif CR. The process of making this tourist animation includes 3 stages, namely pre-production, production and post-production. While the design model used is a descriptive procedural model, which outlines the steps that must be taken to produce the product. This design produces 2 characters and 8 3-dimensional properties along with a combination of 2-dimensional animation that is harmonized into an animated video unit with a duration of 3 minutes 20 seconds. Keywords: animation, 3-dimension, tourism